Reproductive biology of the Iberian species of Potentilla L. (Rosaceae) - Antonio Guillén; Enrique Rico; Santiago Castroviejo (Anales del Jardín Botánico de Madrid)
Several processes related to the reproductive biology of the Iberian species of the genus Potentilla L. subg. Trichothalamus (Spreng.) Rchb., Comarum (L.) Syme and Fragariastrum (Heist. ex Fabr.) Rchb. are studied. We provide data concerning compatibility, agamospermy and hybridization along with pollination and fruit dispersal. No agamospermy mechanisms were found in any of the taxa, nor were there signs of any hybridization, although potential signs of self-incompatibility were detected. Regarding to pollination, a marked tendency toward autogamy was observed in certain groups. Finally, some mechanisms for the release and dispersal of diaspores are described in relation to diaspore and flower receptacle morphology.